Analisis Pemenuhan Kewajiban Pajak Penghasilan Pasal 22 Bendahara Dinas Kesehatan Kabupaten Ogan Komering Ilir - Melati Mustika Arditia; Antonius Ragil Kuncoro (Politeknik Keuangan Negara STAN, 2022)
Income Tax Article 22 is one type of tax that is collected using the withholding system method. The success of this withholding system method is highly dependent on a third party appointed as the withholding agent or tax collector. This study aims to evaluate the implementation of Income Tax Article 22 duty of Treasurer of Ogan Komering Ilir district health office based on tax regulation in the year of evaluation, identify, and promote solutions to overcome the obstacle. This study used exploratory qualitative approach. Data was obtained by literature study, documentation, and semi-structured interview. The results showed that implementation of Income Tax Article 22 duty of Treasurer of Ogan Komering Ilir district health was not fully compatible with tax regulation. Major obstacle of the incompatibility was lack of understanding of the treasurer regarding the obligation to report income tax article 22 caused by lack of socialization and tax information among related parties, especially tax authority.